PENGARUH EKSPOR MIGAS, PENANAMAN MODAL ASING, UTANG LUAR NEGERI, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Warer, Insyai Rina; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
This study aims to analyze the partial and simultaneous effect of oil and gas exports, foreign investment, foreign debt and inflation on Indonesia's economic growth in 1975-2019. The research method uses a quantitative approach which will be explained associatively. The data analysis used is multiple linear regression method as an econometric tool to describe the characteristics of a sample or observed location with the help of SPSS 26 for windows. The results of the study prove that partially oil and gas exports, foreign debt, and inflation affect Indonesia's economic growth. Meanwhile, foreign investment has no effect on Indonesia's economic growth. Simultaneously, the variables of oil and gas exports, foreign investment, foreign debt and inflation affect Indonesia's economic growth. This is supported by the R2 value of 0.599 which means that 59.9 percent of the variation in economic growth is influenced by oil and gas exports, foreign investment, foreign debt and inflation, while the remaining 40.1 percent is influenced by other factors not included in the model.